ANALISIS PENGARUH PENERAPAN MEKANISME CORPORATE GOVERNANCE TERHADAP KEMUNGKINAN PERUSAHAAN MENGALAMI KONDISI FINANCIAL DISTRESS (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Andhika Yudha; Fuad Fuad (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to examine the effect of corporate governance mechanisms on the likelihood of a company experiencing financial distress. Indicators used to measure corporate governance mechanism in this study is the size of the board of commissioners, proportion of independent commissioners board, managerial ownership, institutional ownership, and managerial agency costs. While financial distress as the dependent variable was measured using the Altman Z -score . This study uses secondary data to the entire population of companies listed in Indonesia Stock Exchange ( IDX ) 2010-2012. The method used to determine the sample using purposive sampling. The analytical method used is the ordinal logistic regression. Results of hypothesis testing showed that the size of the board of commissioners, institutional ownership, and agency costs have no significant effect on the likelihood of financial distress. While the proportion of independent commissioners and managerial ownership significantly affect the likelihood of financial distress.